Testing, revision and application of the social anxiety scale for Chinese social media users - Wang, Yaning; Zhang, Huan; Bao, Sarenna (Frontiers in Psychology, 2024)
This study aims to modify the Social Anxiety Scale for Social Media Users (SAS-SMU) to make it more suitable for assessing social anxiety among Chinese social media users, taking into account the unique cultural nuances and social media usage patterns in China. Consequently, a systematic approach was adopted, involving three distinct studies. Study 1 involved translating the English scale into Chinese, conducting interviews with Chinese social media users, and subsequently revising the scale items based on the interview data to ensure cultural appropriateness. Study 2 employed an online survey to collect data and examine the reliability and construct validity of the revised scale, including a two-phase approach: an exploratory factor analysis (EFA) was conducted with 500 participants to identify the underlying factor structure, and a subsequent confirmatory factor analysis (CFA) with 408 participants was used to cross-validate the results. Thus far, this study has developed a social anxiety scale for Chinese mobile social media users (SAS-CMSMU) consisted of 11 items on three factors: Interaction Anxiety, Privacy Concern Anxiety, and Shared Content Anxiety. Study 3 (N = 1,006) applied the SAS-CMSMU to assess social anxiety among Wechat users. The results indicated that participants showed a high level of overall social anxiety (M = 3.646 > 3). Specifically, Privacy Anxiety was the most pronounced, followed by Shared Content Anxiety and Interaction Anxiety. Moreover, significant statistical differences in social anxiety levels were found among WeChat users across gender, age, education, income, and relationship status.